Humour Discourse in Internet Memes: An Aid in ESL Classrooms. (June 2019) - Harshavardhan, Vignesh; David Wilson D,; Kumar, Mallika Vijaya
In the ever-changing classroom dynamics of the twenty-first century, teaching needs to be innovative in order to be effective. The youth of the present age are members of virtual societies communicating mostly through the digital medium. This digital communication has its effects on the traditional classroom lectures. There has been a marked decline in basic language skills. Learners are less attentive and need more motivation. Interactive method of teaching is the best method of teaching language. But for this, the learners have to participate in the classroom and contribute something of their own. Learners have to be taught in a method that interests them and makes the language taught to them relevant in context. There is a need to incorporate digital communicative medium inside the language classroom in an enterprising and novel way while maintaining a low affective filter. For this, teachers have to adopt a systematic approach to digital technology. They need to be more versatile and integrate digital information in their daily lesson plans and the classroom activities. This research proposes one such digital age teaching procedure wherein internet memes are used to teach English. Internet memes provide humour and reduce anxiety. They can make the learners attentive and relate to the language learning process.